A3_4 Fly High, Gyroid! - Holland, Katie; Flood, Laura; Leversha, Thomas; Manley, Max (Physics Special Topics, 2022)
In this paper, we investigated whether a small rocket in the game Super Smash Bros. Ultimate would be viable, based on whether it could hold the amount of fuel required to reach its maximum altitude. We found that the volume of liquid hydrogen/liquid oxygen fuel required is less than the volume of the rocket booster, so the rocket would be viable in this sense.